2012
DOI: 10.1007/978-3-642-34014-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Exact Graph Matching with Application in Human Action Recognition

Abstract: Abstract. Graph matching is one of the principal methods to formulate the correspondence between two set of points in computer vision and pattern recognition. However, most formulations are based on the minimization of a difficult energy function which is known to be NP-hard. Traditional methods solve the minimization problem approximately. In this paper, we show that an efficient solution can be obtained by exactly solving an approximated problem instead of approximately solving the original problem. We deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The performances of six approaches on each action class are shown in Figure 3. KTH (%) UCF (%) Yeffet et al [24] 90.1 79.2 Wang et al [22] 92.1 85.6 Kovashka et al [11] 94.5 87.3 Le et al [12] 93.9 86.5 Wang et al [21] 94.2 88.2 Jiang et al [10] 95.8 88.0 Wang et al [23] 93.3 -Celiktutan et al [3] 90.6 -Our 'VCG+VSG+CGKs' 97.0 90.7 Table 2. The comparison of our approach with the state-of-the-art approaches on the KTH and UCF sport datasets.…”
Section: Experiments On the Kth Datasetmentioning
confidence: 98%
“…The performances of six approaches on each action class are shown in Figure 3. KTH (%) UCF (%) Yeffet et al [24] 90.1 79.2 Wang et al [22] 92.1 85.6 Kovashka et al [11] 94.5 87.3 Le et al [12] 93.9 86.5 Wang et al [21] 94.2 88.2 Jiang et al [10] 95.8 88.0 Wang et al [23] 93.3 -Celiktutan et al [3] 90.6 -Our 'VCG+VSG+CGKs' 97.0 90.7 Table 2. The comparison of our approach with the state-of-the-art approaches on the KTH and UCF sport datasets.…”
Section: Experiments On the Kth Datasetmentioning
confidence: 98%
“…In [3,4], we demonstrated that, in the case of spatio-temporal data, hyper-graph 1 matching problem can be solved with bounded complexity by taking into account the sequential nature of time and causality of human actions. In this work, we customize the same approach for aligning the tracked skeleton sequences.…”
Section: Graph-based Sequence Alignmentmentioning
confidence: 99%
“…In this work, we customize our hyper-graph-based method introduced in [3,4] for aligning the tracked skeleton sequences. We first model the spatio-temporal relationship between the skeleton joints by a chain graphical structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the present volume, Ç eliktutan et al propose an approach to solve the point set matching problem for establishing the correspondence between an action, represented by interest points, to a template [14]. In [15], silhouettes are used for action recognition.…”
Section: Action and Activity Recognitionmentioning
confidence: 99%